Experimental Devices to Investigate the Long-Term Stability of Phase Change Materials under Application Conditions - Christoph Rathgeber; Stefan Hiebler; Rocío Bayón; Luisa F. Cabeza; Gabriel Zsembinszki; Gerald Englmair; Mark Dannemand; Gonzalo Diarce; Oliver Fellmann; Rebecca Ravotti; Dominic Groulx; Ali C. Kheirabadi; et al. (Applied Sciences, 2020)
An important prerequisite to select a reliable phase change material (PCM) for thermal energy storage applications is to test it under application conditions. In the case of solid–liquid PCM, a large amount of thermal energy can be stored and released in a small temperature range around the solid–liquid phase transition. Therefore, to test the long-term stability of solid–liquid PCM, they are subjected to melting and solidification processes taking into account the conditions of the intended application. In this work, 18 experimental devices to investigate the long-term stability of PCM are presented. The experiments can be divided into thermal cycling stability tests, tests on PCM with stable supercooling, and tests on the stability of phase change slurries (PCS). In addition to these experiments, appropriate methods to investigate a possible degradation of the PCM are introduced. Considering the diversity of the investigated devices and the wide range of experimental parameters, further work toward a standardization of PCM stability testing is recommended.